Software Development for Speed Trap Radar Control Unit - Abd Rahman, Zulkifli (2004)
Nowadays, speed trap method has been used in most Malaysian states and overseas for reducing road accident rate. Measurement of vehicle speed for the purposes of law enforcement is currently achieved by radar based methods. Radar is one of devices being used by the police enforcer in Malaysia. It is also commonly used abroad where they are fitted in a patrol car. For the past few years, speed trap system in overseas using radar that can be fitted in either the patrol car or at certain fixed location has experienced an interesting development. However, the radar set and other devices that are available in the market today are too expensive. Furthermore, it needs the police enforcer to trap the speed and take picture of targeted speeding vehicle, and storing that information for law enforcement purpose manually.